AI-POWERED DEDUPLICATION IN INVESTMENT BANKING MIDDLE OFFICE - Swamy Biru, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The evolution of AI-powered deduplication systems has revolutionized investment banking middle offices, encompassing data ingestion, similarity detection, machine learning models, natural language processing integration, and operational enhancements. Advanced preprocessing mechanisms, pattern recognition algorithms, and supervised learning approaches have transformed how financial institutions manage and process data. The implementation demonstrates marked improvements in trade reconciliation, client data management, regulatory compliance, and analytics capabilities. Modern financial data processing, from initial standardization to complex pattern recognition and automated compliance monitoring, has been fundamentally enhanced through artificial intelligence technologies, reshaping middle office operations and setting new industry standards.